Mortality among Critically Ill Acute Kidney Injury Patients Stratified with RIFLE Classification - Jais Kumar; Hassan Mumtaz; Arsh Zahoor; Naveed Sarwar; Kishore Kumar; Shahzaib Ahmad (Journal of Renal and Hepatic Disorders, 2021)
Acute kidney injury, also referred to as AKI, is a common complication seen in critically ill patients . There has been a significant increase in the number of AKI cases over the past few decades. In order to standardize the classification of AKI, the RIFLE (Risk, Injury, Failure, Loss, End-Stage) and AKIN (AKI Network) criteria were developed. This is a prospective, observational, and longitudinal cohort study where data from all patients admitted to the hospital intensive care unit (ICU) were collected. The study duration ranged from March 2019 to September 2020. During the study period, 198 patients were admitted to the ICU. Of these, 69 were excluded while the remaining 104 patients were included in the study. About 66–67% of the total critically ill patient population admitted in the ICU suffer from some etiology related to AKI. Our study highlights the aspect in which the cases of AKI are underreported. RIFLE class R or class I is still associated with excess mortality compared with patients who maintained normal function. RIFLE is a reliable system of classification, which is well classified and indicates the immediate necessity of renal replacement therapy (RRT); the prognosis of early RRT is fairly good in critically ill patients with AKI.